Comparison of caudal analgesia between ropivacaine and ropivacaine with clonidine in children: A randomized controlled trial - Arpita Laha; Sarmila Ghosh; Haripada Das (Saudi Journal of Anaesthesia, 2012)
Background: Addition of clonidine to ropivacaine (0.2%) can potentially enhance analgesia without producing prolonged motor blockade. The aim of the present study was to compare the post-operative pain relieving quality of ropivacaine 0.2% and clonidine mixture to that of plain ropivacaine 0.2% following caudal administration in children. Methods: In a prospective, double-blinded, randomized controlled trial, 30 ASA 1 pediatric patients undergoing infraumbilical surgery were randomly allocated to receive a caudal injection of either plain ropivacaine 0.2% (1 ml/kg) (group A) or a mixture of ropivacaine 0.2% (1 ml/kg) with clonidine 2 μg/kg (group B). Objective pain score and need for supplemental analgesics were compared during the 1 st 24 hours postoperatively. Residual post-operative sedation and motor blockade were also assessed. Results: Significantly prolonged duration of post-operative analgesia was observed in group B (P<0.0001). Heart rate and blood pressure were not different in 2 groups. Neither motor blockade nor post-operative sedation varied significantly between the groups. Conclusion: The combination of clonidine (2 μg/kg) and ropivacaine 0.2% was associated with an improved quality of post-operative analgesia compared to plain 0.2% ropivacaine. The improved analgesic quality of the clonidine-ropivacaine mixture was achieved without causing any significant degree of post-operative sedation or prolongation of motor blockade.